Ionizing radiation and restriction enzymes induce microhomology-mediated illegitimate recombination in Saccharomyces cerevisiae - Chan, Cecilia Y. (Oxford University Press, 2007)
DNA double-strand breaks can be repaired by illegitimate recombination without extended sequence homology. A distinct mechanism namely microhomology-mediated recombination occurs between a few basepairs of homology that is associated with deletions. Ionizing radiation and restriction enzymes have been shown to increase the frequency of nonhomologous integration in yeast. However, the mechanism of such enhanced recombination events is not known. Here, we report that both ionizing radiation and restriction enzymes increase the frequency of microhomology-mediated integration. Irradiated yeast cells displayed 77% microhomology-mediated integration, compared to 27% in unirradiated cells. Radiation-induced integration exhibited lack of deletions at genomic insertion sites, implying that such events are likely to occur at undamaged sites. Restriction enzymes also enhanced integration events at random non-restriction sites via microhomology-mediated recombination. Furthermore, generation of a site-specific I-SceI-mediated double-strand break induces microhomology-mediated integration randomly throughout the genome. Taken together, these results suggest that double-strand breaks induce a genome-wide microhomology-mediated illegitimate recombination pathway that facilitates integration probably in trans at non-targeted sites and might be involved in generation of large deletions and other genomic rearrangements.